Design And Simulation Of Finite Element Analysis (Fea) 360º Rotating Table For Video Display Using Autodesk Inventor Software - Jaenudin, Ilham; Mardiyana, Dani; Sulaiman, Zaid; Arisandi, Moch Ichsan; Rohman, Fathur (Migration Letters, 2024)
A turntable is a mechanical device that allows an object, in this case a video screen, to rotate in various angles and directions. Although turntables offer attractive visual capabilities, there are various technical issues that can arise related to their design and construction. One common problem is the inability of the turntable frame to withstand certain loads or instability when exposed to external pressure. So an analysis was carried out using the FEA method on a 360° rotary table design with stainless steel 304 and Iron Plate SS400 materials. The results of static analysis using Autodesk Inventor software show a maximum von Mises value of 139.2 MPa, displacement of 0.175 mm and safety factor of 1.49 ul. These results are considered safe because the safety factor value is within the value range (1.25 – 1.5 ul). So the 360° turntable is able to withstand loads during use.